Examining the Relationship Between Economics and Philosophy - Akansel, İlkben; Akansel, İlkben (IGI Global, 2019)
In today's data-driven world, certain infrastructures of society have begun to lose their anthropological traits. Economics, specifically, has started placing importance on quantity over quality, excluding its philosophical perspective. Scientists and associates of economics need to be reacquainted with the psychological aspect of commerce and its significance to humanity. Examining the Relationship Between Economics and Philosophy is an essential reference source that discusses the psychological view of economics as well as its philosophical background. Featuring research on topics such as cognitive science, neoliberalism, and neuroeconomics, this book is ideally designed for scientists, economists, managers, executives, academicians, researchers, and students seeking coverage on the philosophy of the financial system and its impact on competitive markets. © 2022 Elsevier B.V., All rights reserved.
Keywords: [No Keywords]